An Improved Power-Only Measurement Strategy for Calibrating Phased Array Antennas. (12th August 2022) - Li, Shuaizhao; Yu, Zhongjun; Zhang, Qiang; Luo, Yunhua
Abstract : An improved power-only measurement method is proposed to calibrate phased arrays, which is aimed at solving two remaining problems: little contribution of one antenna element's phase shifting to the whole array's power and the ambiguity of solutions. The method includes four steps. Firstly, the random distributed phase of each element is adjusted to guarantee that it is −90° to +90° relative to the reference element. Secondly, the proper number of the elements shifting their phases together is approximately determined. Then, an invertible matrix is formed from the standard Hadamard matrix to split the array into different groups, which applies to an arbitrary number of elements; Finally, the array gets calibrated with an existing method. Numerical simulations and experiments are conducted to validate the effectiveness of the proposed method.